Effect of equivalent salt deposit density on flashover voltage of contaminated insulator energized by HVDC - Salam, M. A.; Ahmad, H.; Saadom, Z.; Budin, R.; Tamsir, T.; Buntat, Z.; Piah, M. A. M. (2000)

(untitled)
In Malaysia, the demand for electric power is increasing day by day due to more consumption of power in the industrial sector. Recently, the high voltage DC transmission lines are under construction near the coastal environments for transmitting the power to the all states of Malaysia. Therefore, there is a concern about the reliability of these systems especially under adverse environmental conditions due to sea salt spray contamination. This reliability of this contaminated insulator can be improved through its performance studies. For this performance study, an analytical expression between flashover voltage and ESDD of the contaminated insulator has been proposed using Dimensional Analysis technique. The results obtained from the analytical expression are compared with the experimental results and in close agreement are found